Overview Between Clustering and Load Balancing - Abdulla Fairuzullah, Ahmad Tajuddin; Noraziah, Ahmad; Abdalla, Ahmed N. (American Scientific Publishers, 2017)
This paper show the strength of cluster and load balancing. It is important to technical people to choose between cluster and load balancing. The cluster computing is becoming more and more popular. The state-of-the-art technological developments and research innovations are pushing clusters into mainstream computing. The high performance cluster provides an approach to parallel processing that yields super computer level performance. This trend makes it very promising to build high performance computing environments by clusters, with various performance measures from which high availability need to be address. However Network Load Balancing provides improved performance, the ability to add additional servers as necessary, and the ability to perform maintenance on any of the servers without any user impact or hardware configuration changes. By using the combination of Load Balancing and multiple, redundant clusters can add and remove clusters with minimal user impact. It is usually involves dedicated software or hardware, such as a multilayer switch or a Domain Name System server to mitigate some added layer for clustering weakness. The focus of this paper to get High availability 24 x 7 which is a characteristic of a system, which aims to ensure an agreed level of operational performance for a higher than normal period.